(untitled) (Modern education and development, 2025)
The problem of treating chronic wounds remains relevant, but the topic of research on the inflammatory process in patients with long-term non-healing burn wounds has not been sufficiently covered in the literature. The article is devoted to the study of the peculiarities of changes in the content of inflammatory markers in patients during the acute period of burn disease and with a duration of the wound process of more than 35 days. The conducted studies indicate the severity of inflammation, which persists despite the age of the process and undoubtedly has an effect on wound healing. Everyone has patients showed a significant increase in the level of C-reactive protein, and a1 - antitrypsin. When assessing the content of α2-macroglobulin (α2 -MG) and haptoglobin (GG), individual variability of these indicators was established. In patients with long-term non-healing wounds, a greater frequency of a decrease in the concentration of α2-MG and an increase in GH was found compared with similar indicators in patients during the acute period of burn disease. The level of ceruloplasmin turned out to be a more stable indicator than other acute-phase proteins and exceeded the limits of Normal values are found in only one patient during the acute period of burn disease, as well as in one patient with long-term non-healing wounds. There was no correlation between changes in the concentrations of the studied acute-phase proteins, except for the found relationship between the level of GH and α2-MG, which indicates compensatory rearrangements leading to increased synthesis of GH neutralizing lysosomal enzymes against the background of reduced α2-MG activity. Analysis of changes in the content of acute-phase blood proteins (a1-antitrypsin, α2-MG, GG) can it can be important in assessing the severity of the course and prognosis of the disease, which will make it possible to outline tactics for regulating the inflammatory process and thereby increase the effectiveness of treatment of chronic wounds in burned patients.